Social Change in Baduy Society from the Perspective of Auguste Comte's Three Stages of Law - Al Munawar, Faishal Agil (Journal of Progressive Law and Legal Studies, 2024)
The Baduy Tribe is a traditional community subgroup of the Sundanese ethnic group located in the Lebak Regency, Banten. One of Indonesia's cultural heritages, the Sunda Wiwitan religion, continues to thrive peacefully amidst dense ancient forests, river sources, and the peaks of Mount Kendeng in South Banten. Sunda Wiwitan is the religion of the Baduy people, which honors the spirits of ancestors (karuhun). It is not widely known that the Baduy Tribe has undergone significant religious changes, particularly towards Islam. This research is a normative study using a descriptive-qualitative approach aimed at analyzing the social changes of the Baduy tribe from the perspective of Auguste Comte's Three Stages of Law. The findings of this research indicate that the pattern of social and religious (intellectual) change in the Baduy Society is evolutionary, as the transformation occurs gradually through a continuous self-change process that takes considerable time, in accordance with Auguste Comte's Evolutionary Theory (Three Stages of Law).